Corporate Voluntary Disclosures in Emerging Markets: Empirical Evidence From the GCC Equity Markets - Awad, Antoine B.; Seissian, Lena A.; Gharios, Robert T. (International Journal of Accounting and Financial Reporting, 2022)
In their path of searching for additional sources of information for better-informed decision-making process, market participants are presented with Voluntary disclosures. This paper aims at examining the determinants of voluntary disclosures in the GCC countries. A cross-sectional multiple regression analysis with a sample size of 74 listed firms from the GCC equity markets shows that leverage and economic sectors dominated mainly by “Real Estate” and “Services/Insurance”, have statistically significant impact on voluntary disclosure. A remarkable finding of this paper indicates that the profitability variable measured in terms of return on equity (ROE) significantly explains the variation in the voluntary disclosure score in all sectors except for the “Services/Insurance” one.